Consumers’ Motivational Involvement in eWOM for Information Adoption: The Mediating Role of Organizational Motives - Hussain, Safdar; Song, Xi; Niu, Ben (Frontiers in Psychology, 2020)
E-commerce offers an opportunity on web renounced in internet marketing, and the consumers’ communication behavior has changed, which has taken the place of word of mouth (WOM). This study investigated consumers’ motivational involvement in electronic word of mouth for online information adoption mediated by writers, motivations. Using a sample of 390 active Chinese internet users, it revealed that social tie and perceived risk are essential factors that influence consumers’ behavior, occur unpleasant consequences, and the possibility of uncertainties during the decision making process. Online retailers should emphasize perceived risk mitigation enable to provide a quick response on the websites. Practitioners need to understand consumer behavior in the online shopping system for the expansion of the online marketplace to product varieties, online advertising, retail strategies, and market segmentation. Organizations should train their service provides to timely response, concentrate on monitoring the aspects of consumers’ reviews, on creating choices among groups and individuals, which can improve the organization’s business performance.